2008
DOI: 10.1111/j.1365-277x.2008.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Does taking vitamin, mineral and fatty acid supplements prevent cognitive decline? A systematic review of randomized controlled trials

Abstract: Background Observational studies have shown associations between nutritional status and cognition in later life but evidence from intervention studies is unclear. The present study systematically reviewed the evidence on the effect of nutrient supplementation on cognitive function in people aged ‡65 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 65 publications
1
36
0
Order By: Relevance
“…115 Low-fat dairy products may benefit neurocognitive health, 127 while protein and energy supplementation in malnourished people recovering from illness appears to reduce complications and hospital readmissions and increase grip strength. 128 Supplements not supported by the literature included multivitamins, 129,130 B vitamins, [131][132][133] omega-3 fatty acids [134][135][136][137] or supplementing older people without malnutrition with amino acids or protein. 138 High doses of betacarotene, vitamin E and vitamin A are likely to be harmful and should be avoided in older adults.…”
Section: Nutritionmentioning
confidence: 99%
“…115 Low-fat dairy products may benefit neurocognitive health, 127 while protein and energy supplementation in malnourished people recovering from illness appears to reduce complications and hospital readmissions and increase grip strength. 128 Supplements not supported by the literature included multivitamins, 129,130 B vitamins, [131][132][133] omega-3 fatty acids [134][135][136][137] or supplementing older people without malnutrition with amino acids or protein. 138 High doses of betacarotene, vitamin E and vitamin A are likely to be harmful and should be avoided in older adults.…”
Section: Nutritionmentioning
confidence: 99%
“…A systematic review of 22 RCTs (3,442 subjects) that used vitamin B for prevention of cognitive decline, showed no significant effect for the vitamin [215]. In a Cochrane group analysis of 2 clinical trials of individuals with dementia and low serum vitamin B12 levels, treatment with vitamin B12 had no significant effect on cognitive function [216].…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…However, intervention studies with supplements of B vitamins have also found no clear evidence for beneficial effects on cognition (Eussen et al, 2006;McMahon et al, 2006;McNeill et al, 2007;Aisen et al, 2008), except in two studies in populations at increased risk of cardiovascular disease (Durga et al, 2007;Kang et al, 2008). Systematic reviews of the effect of supplements of B vitamins (Balk et al, 2007;Malouf and Grimley Evans, 2008) or multivitamins, multiminerals and fatty acids (Jia et al, 2008a) also concluded that there was no consistent evidence for a beneficial effect of supplementation.…”
Section: Introductionmentioning
confidence: 99%